JURIDICAL ANALYSIS OF THE EFFECTIVENESS OF ONLINE SINGLE SUBMISSION (OSS) IMPLEMENTATION RELATED TO LICENSING OF ENVIRONMENTAL PROTECTION AND MANAGEMENT IN BATAM CITY (Research Study at the Batam City One Stop Integrated Service Investment Service (PTSP) - Idham, Idham; Washliaty, Laily; Siadari Parohha, Lagat (RADJA PUBLIKA, 2022)
friedman and applied theory using the theory of the law of happiness (utilitarianism) by Jeremy Bentham. The results of the analysis concluded, the Effectiveness of the Implementation of Online Single Submission (OSS) which aims to facilitate investment as a framework for accelerating and increasing investment and business, by implementing electronic business licensing with integrity.